دراسة اقتصادية لإنتاج الإكي دنيا في محافظة اللاذقية - خضور ايهاب; عليو محمود (Latakia University Journal -Biological Sciences Series, 2019)
أجريت الدراسة في عدد من المزارع المنتجة للإكي دنيا في محافظة اللاذقية, بهدف حساب متوسط التكاليف والعوائد الإنتاجية لدنم واحد في السنة العاشرة من الزراعة (سنة الوصول إلى الإثمار الاقتصادي), وتقدير بعض المؤشرات الاقتصادية لهذا النوع من المشاريع الزراعية ومنها معامل الربحية ومعامل الريعية ومؤشر فترة استرداد رأس المال المستثمر. بلغت التكاليف الإنتاجية الإجمالية لزراعة دنم بأشجار الإكي دنيا (56900ل.س/دنم), في حين بلغت العوائد الإنتاجية (110000 ل.س/دنم), بناتج إجمالي صافي وقدره (90028 ل.س/دنم), ودخل مزرعي وقدره (57798ل.س/دنم), وبلغ الربح الاقتصادي (53100ل.س/دنم), وكان معامل الربحية (93%) قياساً لرأس المال المستثمر, و(132%) قياساً لتكاليف الإنتاج الأولية, وبلغ معامل الريعية (158%) قياساً لرأس المال المستثمر, و(224%) قياساً لتكاليف الإنتاج الأولية, وبلغ زمن استعادة رأس المال المستثمر(1.07سنة). The study has been done in many farms which are producing the loquat in Lattakia in order to calculate the average of the productive costs and returns per a donum. In the 10th year of planting (the trees get to the stage of the economic profit). It also contains the evaluation of some of the economic parameters to this type of the agricultural projects including the profitability coefficient, the rent coefficient and the invested capital refunding period. The total productive costs of the agriculture of loquat’s trees per an acres have reached (56900 S.P/donum) while the productive returns have reached (110000 S.P/donum). The net total resultant is (90028 S.P/donum) and the farmer income is (57798 S.P/donum) while the economic profit has reached (53100 S.P/donum). The rate of the profitability coefficient is (93%) in relation to the invested capital and it is (132%) in relation to the first production costs. The rate of the rent coefficient has reached (158%) in relation to the invested capital and (224%) in relation to the first production costs. The invested capital refunding period is (1.07y) .